Pathogen corruption and site-directed recombination at a plant disease resistance gene cluster - Nagy, Ervin D.; Bennetzen, Jeffrey L. (Genome Research, 2008)
The Pc locus of sorghum (Sorghum bicolor) determines dominant sensitivity to a host-selective toxin produced by the fungal pathogen Periconia circinata. The Pc region was cloned by a map-based approach and found to contain three tandemly repeated genes with the structures of nucleotide binding site–leucine-rich repeat (NBS–LRR) disease resistance genes. Thirteen independent Pc-to-pc mutations were analyzed, and each was found to remove all or part of the central gene of the threesome. Hence, this central gene is Pc. Most Pc-to-pc mutations were associated with unequal recombination. Eight recombination events were localized to different sites in a 560-bp region within the ∼3.7-kb NBS–LRR genes. Because any unequal recombination located within the flanking NBS–LRR genes would have removed Pc, the clustering of cross-over events within a 560-bp segment indicates that a site-directed recombination process exists that specifically targets unequal events to generate LRR diversity in NBS–LRR loci.
10.1101/gr.078766.108